Is Ambidexterity the Strategy for Navigating the Post-Pandemic Business World? An Exploration of Ambidexterity as a Survival Mechanism for Firms - Nardi, Nazly K.; Charles, Reccia N. (American Journal of Management, 2022)
To be or not to be? - in business - ‘to plan ahead or to respond to the immediate ever-changing situation?’ The key to business survival, as O’Reilley & Tushman (2008) point out, is a company’s ability to engage in both ‘advantage’ and ‘opportunity’ seeking activities simultaneously - ambidexterity. Ambidexterity is a “unique strategic behavior of emerging market multinational enterprises (EM MNEs)” (Luo & Rui, 2009, p. 49). Ambidexterity of strategy showcased by EM MNEs can serve as a blueprint for survival of global businesses facing seismic shifts in the long and short-term environments. Exploring ambidexterity hinges on finding balance, to survive and thrive - traditional and innovative receive unequal focus but duality of focus. Ambidexterity can provide a framework to generate resilient behaviors to face challenging times (Stokes et al., 2018; Weik, 1995). An ambidextrous strategy, paradoxical thinking, planning, and actions will have to be engaged to navigate the way forward. Resulting in overarching questions: does strategic ambidexterity improve the firm's response to business disruptions, and will ambidexterity ensure the firm's competitive advantage and survival?